Temporal vision is related to cognitive function in preadolescent children. Issue 4 (2nd October 2021) - Saint, Sarah E.; Hammond, Billy R.; Khan, Naiman A.; Hillman, Charles H.; Renzi-Hammond, Lisa M.
Abstract: The relation between visual processing speed (critical flicker fusion thresholds [CFF] and psychomotor reaction time) and higher-level cognitive function was assessed using a cross-sectional sample ( n = 51) of 7 to 13-year-old preadolescent children. Data on visual processing speed (CFF and psychomotor reaction time) and cognitive function (Woodcock-Johnson III Tests of Cognitive Abilities) were collected. Woodcock-Johnson III composite standard scores (brief intellectual ability [BIA], cognitive efficiency, processing speed, and executive processes) were calculated to control for age in the cognitive variables. CFF was related to cognitive efficiency, r (46) = 0.26, p = 0.036, and executive processes, r (44) = 0.25, p = 0.05, and showed a trend toward relating to processing speed, r (46) = 0.19, p = 0.09. Both psychomotor reaction time measures (fixed and variable) were related to executive processes and global intelligence (BIA) such that higher cognitive scores were associated with shorter reaction times, r s ranged from −0.25 to −0.29, p s < 0.05. In addition, fixed reaction time was related to cognitive efficiency, r (47) = −0.26, p < 0.05. The small nature of many of these relations suggests that visual processing speed is only one of many possible influences on the higher cognitive function of children.